The personal finance guide for tech professionals : building, protecting, and transferring your wealth - Taulli, Tom, 1968- (Apress, 2022)
Gain a a basic foundation of essential personal finance issues and strategies, specifically geared towards tech professionals. The book will build on the concepts, such as going from the basics of investments to more advanced topics like alternative investments and tax strategies. In the U.S., about 6 million tech startup employees have stock options. The result is that this can often be the biggest source of wealth, sometimes reaching into the millions. Yet there are many financial and tax complications that have been aggravated with the transition to remote work. This can mean lower returns and missed opportunities, and in some cases, employees may even be subject to actions from the IRS and local tax agencies. The Personal Finance Guide For Tech Professionals is packed with actionable advice and covers the main areas that any tech professional will face.